PENGARUH MOTIVASI KERJA,KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus di Desa Bercak Asri, Desa Kladi dan Desa Batu Salang Kecamatan Cermee, Kabupaten Bondowoso) - Yasin, Ali; Wahyuni, Ika; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Humans as resources have the ability to think in determining the progress of an organization or agency. The purpose of this research is to analyze and investigate the influence of work motivation, leadership and work discipline on the performance of village officials with job satisfaction as an intervening variable (Case Study in Bercak Asri, Kladi and Batu Salang Villages, Cermee District, Bondowoso Regency). This research is quantitative research. The population in this study were Bercak Asri village officials, Kladi village and Batu Salang village. The sampling technique uses saturated samples. Hypothesis testing analysis uses Partial Least Square Structural Equation (PLS-SEM). The results of direct effect hypothesis testing using Smart PLS 3.0 show that Motivation has a positive but not significant effect on Job Satisfaction, Motivation has a positive and significant effect on Performance, Leadership has a positive and significant effect on Job Satisfaction, Leadership has a positive but not significant effect on Performance, Work discipline has an effect positive but not significant on Job Satisfaction, Work Discipline has a positive but not significant effect on Performance, and Job Satisfaction has a positive and significant effect on Performance. The results of testing the indirect impact hypothesis show that Motivation has a positive but not significant effect on Performance through Job Satisfaction, Leadership has a positive and significant effect on Performance through Job Satisfaction and Work Discipline has a positive but not significant effect on Performance through Job Satisfaction.